Du personnel au politique : construction d’une identité militante dans le journal d’Alice Stone Blackwell (1872-1874) - Claire Sorin (Amnis)
How does political commitment influence private writings, and how do private writings shape public voices? For Alice Stone Blackwell, the daughter of American feminist Lucy Stone, diary-writing was not merely a Victorian pastime and discipline. Explicitly endowed with an introspective dimension, her journal also enabled her to inscribe her commitment to various public causes in the complex pattern of her identity. Through her private writings, Alice staged and tested her own voices, dealt with her « wild » temper, and above all rejected the ideal of « true womanhood ». The most striking feature of her journal is indeed the glorification of a free mind embodied in a strong and healthy body capable of investing the public sphere. Thus, her positive identification with a powerful body can be interpreted as a political act.